Analysis of intracranial lesions in patients with HIV-associated cryptococcal meningitis - Song, Wei; Liu, Li; Qi, Tangkai; Wang, Zhenyan; Tang, Yang; Sun, Jianjun; Xu, Shuibao; Yang, Junyang; Wang, Jiangrong; Chen, Jun; Zhang, Renfang; Shen, Yinzhong (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundIntracranial imaging abnormalities are commonly observed in patients suffering from HIV-associated cryptococcal meningitis, both before and during the treatment period. This study aims to analyze the prevalence, origins, radiological characteristics, treatments, and prognosis of intracranial lesions in patients with HIV-associated cryptococcal meningitis, thereby providing references for future clinical decision-making.MethodsThe clinical data of patients diagnosed with HIV-associated cryptococcal meningitis and admitted to the Shanghai Public Health Clinical Centre between 2013 and 2019 were collected. Logistic regression analysis was subsequently conducted to identify potential risk factors associated with the development of intracranial lesions in this patient group.ResultsOf 211 patients analyzed, 64.5% (136/211) had intracranial lesions during treatment and follow-up. Initial cranial imaging showed 60% had lesions pre-treatment. Throughout treatment, 32.7% (52/159) developed new or worsened lesions. Mortality rates at 2 weeks, 8 weeks, and 2 years for those with detected lesions were 3%, 7.6%, and 13.2%, respectively. Lesions were primarily caused by Cryptococcus (70.5%) and Mycobacterium (24.3%). Lacunar infarcts, especially in the basal ganglia, were the most common type. Patients aged 50 years or older, and those presenting with altered mental status upon admission, were found to be more likely to have intracranial lesions at baseline, with adjusted odds ratios of 5.364 (95% CI: 1.468-19.591, P=0.011) and 7.970 (95% CI: 2.241-28.337, P=0.001), respectively. Patients with lesion progression showed higher levels of IFN-γ, IL-4, IL-5, IL-6, IL-1Ra, IL-1β, GM-CSF, Eotaxin, and Basic FGF in cerebrospinal fluid after four weeks of treatment.ConclusionIntracranial lesions in HIV-associated cryptococcal meningitis patients are mostly due to Cryptococcus and Mycobacterium infections. They often appear as lacunar infarcts, predominantly in the basal ganglia, and can worsen with treatment initiation, possibly due to higher baseline cytokine levels in cerebrospinal fluid.